Host-seeking Aedes aegypti linked to dengue seropositive households at northeasternMexico - Garza Hernandez, Javier Alfonso (2021)
Background & objectives: Dengue is endemic in the cities along the USA-Mexico border where accurate interventions against Aedesaegypti are required to curb transmission. Here, we examined the link of 11 entomological variables with households (HHs) seropositive(Y=1) or seronegative (Y=0) depending on the proportion of seropositive participants/total participants per HH, and identified the DENVserotypes in mosquito vectors.